Four channel 6.5 kV, 65 A, 100 ns-100 mu s generator with advanced control of pulse and burst protocols for biomedical and biotechnological applications - Kandratsyeu, Aleh (2022)
Featured Application Pulsed generator for biomedical and biotechnology applications. Pulsed electric fields in the sub-microsecond range are being increasingly used in biomedical and biotechnology applications, where the demand for high-voltage and high-frequency pulse generators with enhanced performance and pulse flexibility is pushing the limits of pulse power solid state technology. In the scope of this article, a new pulsed generator, which includes four independent MOSFET based Marx modulators, operating individually or combined, controlled from a computer user interface, is described. The generator is capable of applying different pulse shapes, from unipolar to bipolar pulses into biological loads, in symmetric and asymmetric modes, with voltages up to 6.5 kV and currents up to 65 A, in pulse widths from 100 ns to 100 mu s, including short-circuit protection, current and voltage monitoring. This new scientific tool can open new research possibility due to the flexibility it provides in pulse generation, particularly in adjusting pulse width, polarity, and amplitude from pulse-to-pulse. It also permits operating in burst mode up to 5 MHz in four independent channels, for example in the application of synchronized asymmetric bipolar pulses, which is shown together with other characteristics of the generator.